Cavity ring-down spectroscopy of the fifth overtone of CO. (January 2017) - Tan, Y.; Wang, J.; Zhao, X.-Q.; Liu, A.-W.; Hu, S.-M.
Abstract: The extremely weak 6–0 absorption band of the 12 C 16 O molecule was recorded for the first time using a very sensitive cavity ring-down spectrometer. Frequencies of a few atomic transitions in the 0.8 μm region, transferred to the passive modes of a thermally stabilized Fabry-Pérot interferometer, are used to calibrate the observed spectra with an absolute accuracy of 3×10 −4 cm −1 . Line parameters, including line positions, intensities, self-broadening and -shifting coefficients were derived by fitting the observed spectra with the Voigt profile. Abstract : Highlights: First observation of the 6–0 band of CO. Upper-level energies determined with an accuracy of 3×10 −4 cm −1 . Line parameters of the 6–0 band of 12 C 16 O are presented.